Probing zeolites by vibrational spectroscopies. (5th October 2015) - Bordiga, Silvia; Lamberti, Carlo; Bonino, Francesca; Travert, Arnaud; Thibault-Starzyk, Frédéric
Abstract : This review addresses the most relevant aspects of vibrational spectroscopies (IR, Raman and INS) applied to zeolites and zeotype materials: acidity, basicity and site accessibility investigated by probes molecules; precise determination of the IR absorption coefficients; thermodynamic aspects of molecular adsorption; space and time resolved experiments. Abstract : This review addresses the most relevant aspects of vibrational spectroscopies (IR, Raman and INS) applied to zeolites and zeotype materials. Surface Brønsted and Lewis acidity and surface basicity are treated in detail. The role of probe molecules and the relevance of tuning both the proton affinity and the steric hindrance of the probe to fully understand and map the complex site population present inside microporous materials are critically discussed. A detailed description of the methods needed to precisely determine the IR absorption coefficients is given, making IR a quantitative technique. The thermodynamic parameters of the adsorption process that can be extracted from a variable-temperature IR study are described. Finally, cutting-edge space- and time-resolved experiments are reviewed. All aspects are discussed by reporting relevant examples. When available, the theoretical literature related to the reviewed experimental results is reported to support the interpretation of the vibrational spectra on an atomic level.